Arte, artefatos, cognição: evolução e processos comunicativos - Oliveira, Adriana Gomes de (2004)
The strict relationship between art, crafts and evolution is discussed in this work through approaches that. showing a flow of continuous information between individuais and environments, constitute themselves communicative processes Creation and manipulation of technologies are directly linked to perceptive and cognitive changes that exist not only in the organisms that exploit them but also in those that experience the environment modified by such processes, which are co-evolutionary. Art, ie. a field of reorganization and reconstruction of possibilities for action and perception within reality, when associated to technological tools that carry selforganizational and adaptable potentials, presents differentiated possibilities before it materializes. stimuli that, through repetition, contribute to the permanence of the organism in a certain environment wiutend to remain in time, showing an inner link between the perceptive-neuromotor apparatuses that structure the organisms' cycles of perception/action in their environments, through different evolutionary times. In the body/environment transit of information, art is a fertile terrain to generate sensitive and germinating information